Anticlerical Transfeminist Artivism in Buenos Aires: ARDA and its Symbolic Appropriations of Fire - Fogelman, Patricia (Meridional. Revista Chilena de Estudios Latinoamericanos, 2023)
From a perspective built from cultural studies, the central question of this text will revolve around the symbolic role that fire plays in artivist feminist discourses and performances. Within the spectrum of groups and actions, it focuses on three performances by ARDA, feminist artivist collective, carried out in the city of Buenos Aires: the first, at the obelisk on March 8, 2019 (the day of the International Women's Strike), the second, in front of the cathedral on June 3, 2018 during the Ni Una Menos (NUM) march and the third, a surprise intervention carried out on July 3, 2022 inside the Pilar church.The appropriations of fire in artivist actions, its plasticity and some of its multiple meanings are analyzed and these appropriations that maintain certain ties with the religious imaginary are linked with representations of a strongly anti-clerical nature.ARDA, was created in 2016 by clodet garcía (poet, playwright, actress and fat and lesbian feminist activist), during a difficult time in Argentina, and sought to break into the public space through group actions and ritualizations to raise awareness of the various femininities and gender-sex dissidences against the Church as an ideologue of violence and oppression together with the hetero-patriarchal system and, at the same time, help to release some of the burdens of traumatic experiences of the participants of the collective.The sources investigated are diverse: performances, poems, posts, interviews, photographs, videos, etc.